EXTRACTION AND FRACTIONATION OF PROTEIN AND BETA AMYLASE ENZYME FROM CILEMBU SWEET POTATO - Natasha, Alana
Sweet potato is one of Indonesia’s local food substance with abundant productivity and can be used as a carbohydrates food source in the form of sweet potato flour. Sweet potato flour industries also produce by-products that contain þ-amylase enzyme, polyphenoloxydase (PPO) enzyme, and sporamine which are beneficial for food and health industries. To encourage the production of enzymes and proteins from sweet potatoes in a commercial and industrial scale, this research conducted in two steps. The first step aims to extract protein from sweet potatoes and determine the effect of the amount of solvent and extraction time on the total protein yield in sweet potato crude extract. Based on the variation of the amount of solvent and extraction time, can be determined the optimum condition that results the highest total protein yield in the sweet potato crude extract. While the second step aims to fractionate the þ-amylase enzyme, PPO enzyme, and sporamine from crude protein extracts obtained from protein extraction at optimum condition. In this research, protein was extracted from Cilembu sweet potato with water as the solvent. The crude protein extract was tested for its soluble protein content by Bradford method and its þ-amylase enzyme activity by Bernfeld method. Then, the protein extract is precipitated at the isoelectric point (pH=3,5) to begin the fractionation process of the þ-amylase, PPO, and sporamine which are dissolved proteins in the crude protein extract. Crude protein extract is fractionated gradually with acetone. Based on this research, it is known that the amount of solvent significantly affect the increase in protein yield of sweet potato crude extract and the highest protein yield is obtained at the ratio of solvent mass to sweet potato of 3 g water/g wet sweet potato with 30 minutes extraction time of 8.62 ± 1.11 g extracted protein/100 g of sweet potato protein (wet basis). Based on the result of enzyme activity assay and mass balance approach, specific activity of þ-amylase enzyme in crude protein extracts of 15.43 U/mg protein increased to about 300 U/mg protein in the fraction rich in þ-amylase enzyme. These result indicates that the fractionation process with acetone succeeded in precipitating the þ-amylase enzyme in protein extract. Based on the assumption of mass balance calculation by Cheng et al., (2014), the estimated dry mass of fraction rich in þ-amylase enzyme, PPO enzyme, and sporamine which can be obtained are 0,12 mg, 0,43 mg, and 9.26x102 mg from 1 kg of Cilembu sweet potato.